Why do high jumpers use a curved approach? - Tan, J. C. C.; Yeadon, M. R. (Journal of Sports Sciences, 2005)
Currently, all elite high jumpers use the Fosbury Flop technique with a curved approach. This suggests that the curved approach presents some clear advantage, although there is no general agreement upon the mechanism or the mechanics. This study aimed to determine the characteristics of the approach curve and to investigate how it contributes to the generation of somersault rotation. A simple theoretical model was used to demonstrate that a tightening approach curve would change the inward lean towards the centre of the curve into outwards lean. Three-dimensional video analysis was used to record the performances of two elite male high jumpers in competition. It was found that in each case the radius of the approach curve and the inward lean angle both decreased towards the end of the approach. The amount of outward lean angular velocity generated was shown to be a major proportion of the required somersault angular velocity for a jump. It was concluded that the main advantage of a curved approach was that it resulted in the generation of somersault velocity providing the curve tightened towards the end of the approach.